Audit Graduation Information System (SIMUDAPAPI) in Udayana University using COBIT 5 in Deliver, Service, and Support Domain - Anak Agung Gede Oka Kessawa Adnyana; I Nyoman Darma Kotama; Ida Bagus Alit Swamardika (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Udayana University have a graduation system that need to be assessed to get a good measure of the capability level, an audit based on COBIT 5 based on Delivery, Service, and Support that contain 6 processes conducted to obtain the results. SIMUDAPAPI(Sistem Informasi Wisuda Paperless Integrated) got best capability level DSS02 (2,76) shows the highest capability level, Which means the system able to handle incident and providing quick solutions, and the lowest achieved by DSS06 with 2,5. The gaps still have not been filled and there will be a required changes to improve SIMUDAPAPI Udayan University